Dark triad and depression: The moderating effect of gender - Gómez-Leal, Raquel; Megías-Robles, Alberto; Cabello-González, Rosario; Gutiérrez-Cobo, María José; García Fernández-Abascal, Enrique; Fernández-Berrocal, Pablo (My University, 2019)
The Dark Triad (DT) is composed of three closely related personality traits: Psychopathy, Narcissism, and Machiavellianism. These traits have been linked to emotional deficits. The aim of the current study was to explore how the three personality traits comprising the DT could be related to depression symptoms. For this purpose, a total of seven hundred fifty-two adults (M = 35.60 years) completed a questionnaire battery including DT and Depression measures. Our findings revealed that there are a series of factors characterising individuals with high DT scores that can be related to depression problems. The sub-dimensions of callous affect, interpersonal manipulation, and criminal tendencies for psychopathy, cynical view of human nature for machiavellianism, and entitlement, self-sufficiency, and vanity for narcissism are the factors that best predicted possible depression symptoms. Furthermore, the effect of these factors on depression was a function of gender. These findings may be an excellent tool for the development and implementation of better prevention and treatment programs aimed at decreasing the negative consequences suffered by individuals with high DT scores, which could potentially benefit both clinical practice and society in general. In addition, our results also indicate the importance of considering the effects of gender in the studied relationships.
Keywords: Depresión mental; Depression; Dark triad; Psychopathy; Machiavellianism; Narcissism